Serum concentrations of matrix metalloproteinase-9, tissue inhibitor of matrix metalloproteinase-1 and alpha2-macroglobulin in healthy subjects after supplementation with different doses of marine n-3 fatty acids - Vogt, J.; Andersen, V. L.; Andreasen, A.; Obel, T.; Christensen, J. H.; Schmidt, E. B. (Cellular and Molecular Biology, 2010)
bjective: Extracellular matrix modification by matrix metalloproteinase-9 (MMP-9), tissue inhibitor of matrix metalloproteinases-1 (TIMP-1) and Î±2-macroglobulin may affect the stability of atherosclerotic plaques. Marine n-3 polyunsaturated fatty acids (n-3 PUFA) may protect against plaque rupture. The aim was to investigate the effect of marine n-3 PUFA supplementation on serum levels of MMP-9, TIMP-1, and Î±2-macroglobulin. Methods: Healthy volunteers were randomized to receive capsules contributing either 6.6 g marine n-3 PUFA/day, 2.0 g marine n-3 PUFA/day or 6.6 g of olive oil (control). Serum MMP-9, TIMP-1 and Î±2-macroglobulin was measured at baseline and after 12 weeks of supplementation. One way ANOVA or Kruskal-Wallis test was used to compare groups. Results: 60 healthy volunteers were enrolled and no subjects dropped out of the 12 week study. There were no statistically significant changes in serum levels of MMP-9, TIMP-1, and Î±2-macroglobulin in any of the three treatment groups (P=0.85, P=0.23 and P=0.87, respectively). Conclusion: Supplementation with marine n-3 PUFA had no effect on serum levels of MMP-9, TIMP-1 and Î±2-macroglobulin in healthy subjects. The possible protection offered by marine n-3 PUFA against plaque rupture is therefore unlikely to be mediated through a change in serum levels of MMP-9, TIMP-1 and Î±2-macroglobulin.